Antibacterial Activity of Tunicata Ethanol Extract Polycarpa Aurata gainst Escherichia Coli and Salmonella Typhi by TLC-Bioautography and Agar Diffusion - Selviati, Ratmi; Herwin, Herwin; Nuryanti, Siska (Journal Microbiology Science, 2024)
Tunicata Polycarpa aurata contains chemical compounds in the form of peptides and alkaloids  that are cytotoxic and have the ability as antibacterial against several pathogenic bacteria. The aims of this study was to determine the antibacterial activity of the ethanol extract of Tunicata Polycarpa aurata using the TLC-bioautography and diffusion method. Tunicata Polycarpa aurata was extracted by maceration and then evaporated to obtain a thick extract. The results of the antibacterial screening test showed the active extract at a concentration of 0.1% against Escherichia coli and Salmonella typhi. The results of testing for antibacterial activity using the TLC-bioautography with using ethanol: ethyl acetate (1:4) eluent showed results of Salmonella typhi bacteria with an Rf value = 0.27 and Escherichia coli bacteria with an Rf value = 0.27. While the results of testing the antibacterial activity the using the agar diffusion method showed the largest inhibition zona diameter at a concentration of 4% for Escherichia coli bacteria with an inhibition zone diameter of 12.55 mm, and Salmonella typhi with an inhibition zone diameter of 12.3 mm. Phytochemical screening tests on the ethanol extract of Tunicata Polycarpa aurata revealed  the presence of flavonoids, tannins, steroids/terpenoids, alkaloids and saponins.